Clidicus chinensis n. sp. from Hainan, the first species of the Mastigitae from China (Coleoptera: Staphylinidae: Scydmaeninae) - Zhou, De-Yao; Li, Li-Zhen (Zootaxa, 2015)
The first species of the mastigite genus Clidicus Laporte (Coleoptera: Staphylinidae: Scydmaeninae) from China is described, under the name of Clidicus chinensis n. sp. The type material has been collected in Jianfengling (Hainan prov.); the habitus, aedeagus and spermatheca of the new species are illustrated.